More bucks, more growth, more justice? The effects of regional structural funds on regional economic growth and convergence in Germany - Jonathan Eberle; Thomas Brenner (Philipps-University Marburg, Department of Geography, 2016)
This paper analyzes the impact of the German structure program "Joint Task for the Improvement of Regional Economic Structures" (GRW) on regional economic growth. The paper extends the existing literature by several aspects. First of all, using the popular augmented Solow model by Mankiw et al. (1992) as starting point, we develop an enhanced growth model by including employment as well as technological spatial spillovers to the model. Secondly, the program has not been analyzed within a dynamic spatial panel framework on the level of the 402 German small scale regions before. We use a detailed dataset on this regional level and address the problem of endogeneity by using a System Generalized Method of Moments (GMM) estimator. Finally, we investigate the impact of regional conditions on the effects of the GRW program. The results illustrate that the impact of public subsidies is overestimated in the current literature. In fact, the infrastructure program even emanates a negative direct impact on regional economic growth, especially in sparely populated regions as well as in non-innovative regions.
Keywords: C23; R11; R48; O47; 330; Regional economic growth; ß-convergence; Structural funds; Spatial panel econometrics; Generalized Methods of Moments (GMM) Estimation